The relationship between nutrition in infancy and cognitive performance during adolescence - Nyaradi, A.; Oddy, W.; Hickling, S.; Li, Jianghong; Foster, Jonathan (Frontiers, 2015)
Objectives: In this study, we aimed to investigate the long-term associations between breastfeeding duration during infancy, diet quality as measured by a diet score at 1 year of age, and cognitive performance during adolescence. Methods: Participants (n = 717) were recruited from the West Australian Pregnancy Cohort (Raine) Study, a prospective longitudinal study of 2868 children and their families based in Perth, WA, Australia. Breastfeeding duration and an early diet score at age 1 year were used as the main predictor variables, while a computerized cognitive battery (CogState) was used to assess adolescents’ cognitive performance at 17 years. The diet score, which has seven food group components, was based on a 24-h recall questionnaire completed by the mother at 1 year of age. A higher diet score represents a better, more nutritious eating pattern. Associations between breastfeeding duration, diet score, and cognitive performance were assessed in multivariable regression models. Results: Higher diet scores at 1 year representing better diet quality were significantly associated with faster reaction times in cognitive performance at 17 years [Detection Task (DET): β = −0.004, 95% CI: −0.008; 0.000, p = 0.036; Identification Task (IDN): β = −0.004, 95% CI: −0.008; 0.000, p = 0.027]. Breastfeeding duration (≥4 months) was also significantly associated with a shorter reaction time, but only for males (DET: β = −0.026, 95% CI: −0.046; −0.006, p = 0.010). Conclusion: Nutrition in early childhood may have a long-term association with fundamental cognitive processing speed, which is likely to be related to enhanced brain development in the first year of life.